Zegarki Tyszkiewiczów. Część pierwsza - Zieliński, Jan (Załącznik Kulturoznawczy, 2020)
A free narrative about several watches – real ones and those described in literature – related with the wealthy Polish-Lithuanian Tyszkiewicz family in the 18th and 19th century. Lengthy digressions touch several aspects of life in that period. One concerns the person of Ludwik Skumin Tyszkiewicz (1748–1775), a talented orator who lived a dangerous life and died young in Paris (his ideas are compared with those of Michał Mniszech, who tried to establish a Jaquet-Droz manufacture of Swiss watches in Warsaw). Another one concerns Karol Wyrwicz, who inherited Tyszkiewicz’s watch, a priest who introduced the style of armorials to his parish books; his name is, incidentally, associated with a new Polish word for a corkscrew. The final part discusses the motive of watches in travel notes from Sweden written by Eustachy Tyszkiewicz. To be followed by Part Two.